(untitled) (Journal of Human Sciences, 2023)
This research focuses on the analysis of two main points: first, the Ottoman fiscal taxes on palm trees and their passage into Fezzan district during the Second Ottoman Era, specifically between 1842 and 1875. The second is concerned with the importance of this blessed tree and its production in the artisanal economy of the citizens in Fezzan and its impact on their social property. As we have obtained from the Ottoman Authority’s public and private archival documents, as well as other local documents of some of Fezzan’s financially well-off men who were buying dates from the Ottoman in power at the time, the overall of this unpublished documentary sample highlights these taxes as a whole and brings to light the valuable information they contained, requiring that they be detected, discussed, analysed and compared, and, to the extent possible, utilized. Attempting to approach foreign travellers’ blogs during the period in question with the important source information they contained to identify their description of the palm trees of the Fezzan district, the types of dates, their quality and taxes imposed on them, their impact on the people, and the connection between the latter with the Ottoman Authority and its commanders regarding its taxes, in order to complete the analytical vision on this subject as far as possible; As there are only a few brief references to previous studies specializing in the topic. The disclosure and examination of the content of that new source material in accordance with the historical analytical approach may provide the new and authentic nature of the sections of this research and the possible original outcome of its conclusion.